Study on the Initial Consonant [r] Transliteration Method in Dharani Sutra of Amoghavajra - Keawsuwan, Chatuwit (Journal of Sinology (วารสารจีนวิทยา), 2017)
This article presents the Dharani sutra transliteration by Amoghavajra. It is a sutra of mantraya-na Buddhism. The paper assorts 4 points: mantraya-na Buddhism, Biography of Amoghavajra, The meaning of Dharani sutra and the Initial Consonant ;R= Transliteration method in Dharani Sutra from Sanskrit into Chinese.